1988
DOI: 10.1210/mend-2-11-1077
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Development Specific Regulation of a Complex Family of Rat Insulin-Like Growth Factor I Messenger Ribonucleic Acids

Abstract: To obtain information about the functional significance of the structural heterogeneity that has been described for rat insulin-like growth factor I (IGF-I) cDNAs, we hybridized polyadenylated RNAs from rat tissues at different developmental stages with probes specific for two variant 5'-sequences (designated here as type 1 and type 2), with a probe specific for IB type E domain coding sequences and with a probe for E domain sequences common to IA and IB type IGF-I cDNAs. Northern blot analyses revealed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 27 publications
4
48
0
Order By: Relevance
“…Delafontaine et al (1991) found 2.1-kb and 1.6-kb IGF-I mRNA transcripts in endothelium by northern analysis and concluded that endothelial cells both synthesized and secreted IGF-I. In this report, the IGF-I mRNA transcript observed in endothelial cells was a 7.5-7.0 kb form, identical to that demonstrated in adult porcine and bovine liver, and in other tissues from other species (Hoyt et al, 1988;Lund et al, 1986). In comparison, Sarazani et al (1989) detected a major 7.8-kb IGF-I mRNA in rat aortic tissue and Lund et al (1986) noted that the predominant IGF-I mRNA transcript in nonhepatic tissue was a 7.5-to 7.0-kb form.…”
Section: Discussionsupporting
confidence: 80%
“…Delafontaine et al (1991) found 2.1-kb and 1.6-kb IGF-I mRNA transcripts in endothelium by northern analysis and concluded that endothelial cells both synthesized and secreted IGF-I. In this report, the IGF-I mRNA transcript observed in endothelial cells was a 7.5-7.0 kb form, identical to that demonstrated in adult porcine and bovine liver, and in other tissues from other species (Hoyt et al, 1988;Lund et al, 1986). In comparison, Sarazani et al (1989) detected a major 7.8-kb IGF-I mRNA in rat aortic tissue and Lund et al (1986) noted that the predominant IGF-I mRNA transcript in nonhepatic tissue was a 7.5-to 7.0-kb form.…”
Section: Discussionsupporting
confidence: 80%
“…Serum concentrations of IGF-I are low in the fetal and early postnatal periods compared with adult levels, increasing markedly during puberty (1). It is believed that the adult liver, which exhibits a several order of magnitude higher level of postnatal igf1 gene expression than any other tissue, is the source for circulating IGF-I (22)(23)(24)(25). Sera of 6-week-old mice were examined for the presence of immunoreactive IGF-I ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the rat liver, transcription initiation at exon 2 was reduced in diabetes and fasting. Class 1 transcripts are ubiquitous and predominant in all tissues, and Class 2 transcripts are detected in liver (Hoyt et al, 1988). O'Sullivan et al (2002) studied regulation of class 1 and class 2-IGF-I mRNAs in lamb liver, and showed that GH may stabilize mature class 2-IGF-I mRNA or destabilize mature class 1-IGF-I mRNA and the class 2-IGF-I mRNA may have a greater overall translational potential.…”
Section: Discussionmentioning
confidence: 99%